Hubungan antara Status Gizi, Pola Makan, dan Kecukupan Kalori terhadap Kelelahan Kerja Pengrajin Gerabah Perempuan di Desa Karanganyar, Borobudur, Magelang: Hubungan antara Status Gizi, Pola Makan, dan Kecukupan Kalori terhadap Kelelahan Kerja Pengrajin Gerabah Perempuan di Desa Karanganyar, Borobudur, Magelang - Shela Aprilia; Indriati Paskarini; Tri Martiana; Widarjanto Widarjanto; Santi Wirastri Hayuhaning Budi (Amerta Nutrition, 2023)
Background: Work Fatigue is a common condition often experienced by workers characterized by decreased work performance. Work fatigue can be caused by poor nutritional status, diet and calorie intake received by workers. Objectives: This study purpose is to analyze the relationship between nutritional status, diet, calorie intake and work fatigue experienced by female pottery craftsmen in Karanganya Village, Central Java. Methods: This research is a quantitative analytic research with cross-sectional study design. The study population was 70 female pottery artisans in Karanganyar Village, Borobudur District, Magelang Regency, Central Java. The number of samples taken was 43 people determined using simple random sampling. The variables studied were nutritional status, diet, calorie adequacy and physical labor fatigue. The instruments used were digital weight scales and staturemeter, Food Frequency Questionnaire, 24-hour food recall form and reaction timer. Data analysis techniques using SPSS with Chi-square test and logistic regression. Results: 48,84% of pottery crafters have abnormal nutritional. 65.12% of pottery crafters have a good diet although 69.77% of the calorie adequacy of pottery crafters is not met. 34.88% of pottery craftsmen experienced physical fatigue in the moderate category and 4.65% experienced physical fatigue in the severe category. Based on the results of bivariate analysis, there is a relationship between diet (p=0.010), calorie adequacy (p=0.044) with physical work fatigue. There is no relationship between nutritional status (p=0.098) with physical fatigue. Conclusions: Work fatigue experienced by female pottery crafters in Karanganyar Village is caused by diet and calorie adequacy deficits.